Titanocene(iii) complexes with 2-phosphinoaryloxide ligands for the catalytic dehydrogenation of dimethylamine borane12. Issue 27 (21st July 2015) - Klahn, Marcus; Hollmann, Dirk; Spannenberg, Anke; Brückner, Angelika; Beweries, Torsten
<x xml:space="preserve">Abstract</x> A study of the dehydrogenation of dimethylamine borane using different titanocene(iii) complexes with 2-phosphinoaryloxide ligands is presented.